Improvement in protein separation using a modulated bipolar membrane chromatography technique - Raja Ghosh (Journal of Chromatography Open)
This paper discusses a novel method for improving resolution in protein separation obtained by membrane chromatography. The method is based on a bipolar membrane system involving the synergistic combination of a modulating membrane and a binding membrane for improving peak sharpness, and resolution in bind-and-elute protein separation. In this study, an anion exchange membrane served as the binding membrane while a cation exchange membrane served as the modulating membrane. Significantly sharper peaks were obtained in single-protein bind-and-elute experiments using modulated bipolar membrane chromatography compared to normal anion exchange membrane chromatography, which served as the control. Significantly greater resolution in binary protein separation was also obtained with modulated bipolar membrane chromatography. The working principles of the method are hypothesized in this paper. Modulated bipolar membrane chromatography could potentially be used for high-resolution analytical separation of proteins and other biological macromolecules.